Australia 1:50 000 topographic survey. 8159-1,. Rollingstone - Australia. Army. Royal Australian Survey Corps (Canberra : Royal Australian Survey Corps, 1987)
Topographic map with relief shown by contours and spot heights. Some maps show mean temperature and average annual rainfall graphs.
Index to adjoining maps.
Keywords: Rollingstone Region (Qld.) -- Maps; Topographic maps